The role of convex equity incentives in managers’ forecasting decisions - CHO, Young Jun (Institutional Knowledge at Singapore Management University, 2021)
Prior literature suggests that voluntary disclosures of forward-looking information tend to lead to capital market benefits, but these disclosures may also result in negative capital market consequences if subsequent performance falls below expectations. We, therefore, hypothesize that convex equity incentives, which reward managers for stock price gains while limiting their exposure to losses, should promote greater voluntary forward-looking disclosure. Consistent with our hypothesis, we find a significantly positive association between equity incentive convexity and forecast issuance and frequency. We also find that the positive association is more pronounced for firms with higher sales volatility and managers with shorter tenure, in which cases managers are more concerned with missing their own forecasts. Our study suggests that the risks arising from providing voluntary disclosures are important considerations in managers’ disclosure decisions.